Pengaruh Kualitas Akrual Dan Risiko Pasar Terhadap Sinkronitas Harga Saham - Laila Fitri; Henri Agustin (Universitas Negeri Padang, 2020)
Examine the effect of accrual quality and market risk which is considered as company-specific information on stock price synchronicity. The data used in this study are secondary data on the financial statements and share prices of LQ45 companies in the 2016-2018 period. The data sampling method used was purposive sampling method based on certain criteria. In this study, a sample of 24 companies was obtained. Hypothesis testing in this study uses multiple linear regression analysis. The results prove that the quality of accruals has no significant effect on stock price synchronicity and market risk has a negative and significant effect on stock price synchronicity